Integrated Metabolomics and Proteomics Analysis Reveals Plasma Lipid Metabolic Disturbance in Patients With Parkinson’s Disease - Hu, Ling; Dong, Mei-Xue; Huang, Yan-Ling; Lu, Chang-Qi; Qian, Qian; Zhang, Chun-Cheng; Xu, Xiao-Min; Liu, Yang; Chen, Guang-Hui; Wei, You-Dong (Frontiers in Molecular Neuroscience, 2020)
Parkinson’s disease (PD) is a common neurodegenerative disease in the elderly while the pathogenesis remains unclear. We aimed to explore its pathogenesis by plasma integrated metabolomics and proteomics analysis. The clinical data of consecutively recruited PD patients and healthy controls were assessed. Fasting plasma samples were obtained and analyzed using metabolomics and proteomics methods. After that, differentially expressed metabolites and proteins were identified for further bioinformatics analysis. No significant difference was found in clinical data between these two groups. Eighty-three metabolites were differentially expressed in PD patients identified by metabolomics analysis. These metabolites were predominately lipid and lipid-like molecules (63%), among which 25% were sphingolipids. Sphingolipid metabolism pathway was enriched and tended to be activated in the following KEGG pathway analysis. According to the proteomics analysis, forty proteins were identified to be differentially expressed, seven of which were apolipoproteins. Furthermore, five of the six top ranking Gene Ontology terms from cellular component and eleven of the other fourteen Gene Ontology terms from biological process were directly associated with lipid metabolism. In KEGG pathway analysis, the five enriched pathways were also significantly related with lipid metabolism (p<0.05). Overall, Parkinson’s disease is associated with plasma lipid metabolic disturbance, including the activated sphingolipid metabolism and decreased apolipoproteins.